Factors affecting cattle finishing profitability - Mintert, J.R.; Schroeder, Ted C.; Langemeier, Michael R.; Albright, M.L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The relative contributions of fluctuating cattle performance; interest rates; and feeder cattle, fed cattle, and feed grain prices to profit variability of cattle feeding were examined in this study. Closeout data from 6696 pens of steers placed on feed between January 1980 and May 1991 at two western Kansas custom feedyards were used to estimate the relative impacts of prices and animal performance on cattle feeding profits. Combined, fed and feeder cattle prices explained 70 to 80% of profit variability, depending on placement weight. Overall, cattle prices and feeding costs explained at least 85% of the variation in profitability. Animal performance explained 5 to 10% of profit variability.
Keywords: Beef; Cattle finishing profitability; Sale prices; Feeder cattle prices; Placement weight; Animal performance